ADOPSI TEKNOLOGI DIGITAL DALAM KEPEMIMPINAN KRISTEN DAN IMPLIKASINYA TERHADAP KOMUNITAS IMAN - Rianti Marten Tawa; Sartike Ratte Karua; Arlin Mendonga; Asriani Datu Karua; Opin (Adisam Publisher, 2026)
Christian leadership faces growing demands in the digital era, yet adequate theological and practical guidance remains largely unavailable. This study aims to analyze previous research responses to the challenges of digital technology adoption in Christian leadership and to evaluate its implications for spiritual growth and faith communities. The study employs a systematic literature review method by collecting and analyzing reputable academic journal sources relevant to the research topic. Findings reveal that existing literature has identified substantial opportunities for mission expansion through digitalization, but has yet to offer contextually verified ethical frameworks for adoption. The impact of technology on faith communities works in two directions, expanding worship accessibility while simultaneously risking the erosion of authentic spiritual fellowship. This study concludes that effective Christian leadership in the digital era requires the integration of deep spirituality and adaptive digital competence, ensuring that technology serves as a ministry tool rather than a substitute for genuine faith community.